Creative process engagement for regulating integral and incidental anger - Keith Strasbaugh; Shane Connelly; Jessica Johnston-Fisher (Journal of Creativity)
Research suggests that creative task performance may lead to either more positive or negative mood states depending on the type of creative thinking process engaged. While this literature establishes a relationship with mood states, the effects of creativity on specific discrete emotions (i.e., anger, anxiety) remain unexamined. Additionally, the extent to which discrete emotions that are incidental or integral to task context warrants consideration, as the nature of the emotions felt may affect the extent to which they are regulated through creative task performance. Two laboratory studies were conducted in which participants were randomly assigned to be induced with either incidental or integral state anger or state anxiety, and then either generated ideas (study one) or evaluated ideas (study two) prior to self-reporting their emotional states. Results indicated that while integral and incidental state anger are lessened after generating or evaluating ideas, the extent to which one feels anxiety is unaffected by performing either task. Implications of these findings provide new avenues for emotion regulation research and recommendations for utilizing creative processes to mitigate different types of state anger.